PubMed Assistant: a biologist-friendly interface for enhanced PubMed search - Ding, Jing; Hughes, LaRon M.; Berleant, Daniel; Fulmer, Andy W.; Wurtele, Eve Syrkin (Bioinformatics, 2006)
MEDLINE is one of the most important bibliographical information sources for biologists and medical workers. Its PubMed interface supports Boolean queries, which are potentially expressive and exact. However, PubMed is also designed to support simplicity of use at the expense of query expressiveness and exactness. Many PubMed users have never tried explicit Boolean queries. We developed a Java program, PubMed Assistant, to make literature access easier in several ways. PubMed Assistant provides an interface that efficiently displays information about the citations and includes useful functions such as keyword highlighting, export to citation managers, clickable links to Google Scholar and others that are lacking in PubMed. Availability: PubMed Assistant and a detailed online manual are freely available at under a GPL (GNU General Public License). Contact:berleant@iastate.edu